EPIDEMIOLOGIC PECULARITIES OF TOXOPLASMOSIS IN BUKOVYNA’S WOMEN OF REPRODUCTIVE AGE - Moskaliuk, V.D.; Randiuk, Yu.O.; Sydorchuk, A.S. (Інфекційні хвороби, 2015)
The rate of toxoplasmosis invasion in Bukovyna’s women of reproductive age makes up 81,3 % with the predomination of the rural population (87,3 ± 0,58 %) versus (71,4 ± 1,11 %) urban inhabitants. The rate of detecting seropositive persons based on toxoplasmosis does not differ substantially in age groups ranging from 16 to 39 years, the latter being indicative of their contamination, still before reaching the reproductive age. The case rate of primary contamination with toxoplasmosis among women aged 16- 39 years did not exceed 0,43 %.